Environmentally compatible and highly improved hole transport materials (HTMs) based on benzotrithiophene (BTT) skeleton for perovskite as well as narrow bandgap donors for organic solar cells. (1st January 2022) - Zahid, Saba; Rasool, Alvina; Ans, Muhammad; Salim Akhter, Mohammed; Iqbal, Javed; Al-Buriahi, M.S.; Alomairy, Sultan; Alrowaili, Z.A.
Graphical abstract: Highlights: Five small donor molecules (BTTM1-BTTM5) have been designed for photovoltaic applications. Designed chromophores open up huge optoelectronic properties for organic solar cells and hole transport materials for perovskite solar cells. Researched molecules have manifested enhanced absorption, narrow band gap and formidable charge mobility. Abstract: This research project centralized modeling and DFT analysis of reference (BTTR) and intended chromophores (BTTM1-BTTM5) based on benzotrithiophene (BTT) core to render them as economic competitors for solar cells. Substantial investigation on molecular levels of researched molecules had been accomplished by pursuing computational DFT and TD-DFT simulations to probe photovoltaic characteristics. MPW1PW91/6-311G (d, p) used to analytically observe molecules for their simulated values of absorption maximum, frontier molecular orbitals (FMOs), ionization potential (IP), electron affinity (EA), light harvesting efficiency (LHE), quantum chemical parameters i.e. chemical potential ( μ 0 ), chemical hardness η, chemical softness ( S ), electronegativity χ, and electrophilicity index ( ω ) . Additionally, other geometric variables such as density of state (DOS), electrostatic potential (ESP), transition density matrix (TDM), binding energy (Eb ), dipole moment (μ), reorganization energy (RE), and device performance (VOC ) had been enumerated and contrasted with BTTR. Results uttered that all our modeled molecules (BTTM1-BTTM5) were preferential candidates for electronic properties as a consequence of red-shifted absorption maximum (662 nm) in CHCl3, narrow band gap (1.87 eV), lowest excitation energy (1.91 eV), highest μ (6.55 D), lowest Eb (0.52 eV) and chemically reactivity. Theoretically computed VOC values were found in the range of 1.14 to 1.38 eV with donor molecule PC61 BM after successfully testing the compatibility of donor and acceptor interfaces. Because of the low RE values of electron (λe ) and hole (λh ) of designed chromophores, they exhibited magnified charge mobility. BTTM3 portrayed the lowest λe (0.005679 eV) and BTTM4 had explored the lowest λh (0.006637 eV). All designed chromophores (BTTM1-BTTM5) depicted intensified metrics computationally, which was a convincing rationale for their possible experimental usage in developing solar cell technology.